The Effect of Knowledge Sharing, Absorption Capacity on Employee Performance with Innovation Capability as Intervening Variables (Case Study on Employees of the Central Java Agricultural Technology Research Center) - Nurcahyo, Satria Avianda; Andriyani, Andriyani; Rionaldo, Richo; Soesanto, Harry (Budapest International Research and Critics University, 2022)
This study aims to analyze how much influence the variable knowledge sharing, absorption capacity has on employee performance through innovation capability as an intervening variable. This study uses the Structural Equation Model (SEM) analysis method. The findings of this study indicate that the variable knowledge sharing has a positive effect on employee performance, absorption capacity has a positive effect on employee performance, knowledge sharing has a negative effect on innovation capability, and absorption capacity has a positive effect on employee performance and innovation. Capability has a positive effect on employee performance. The managerial implications in this study indicate that absorption capacity has a positive effect on employee performance and innovation capability has a positive effect on employee performance. The managerial implications in this study indicate that absorption capacity has a positive effect on employee performance and innovation capability has a positive effect on employee performance. The managerial implications in this study indicate that there needs to be optimization in applying the priority of the quality of work results to existing employees. The quality of the work describes the results expected by the government to be applied to local farmers in Central Java. With good yield quality in innovation of superior seeds and fertilizers, it will increase the production power of farmers in Central Java.